Ⅰ-Ⅱ MIXED-MODE FRACTURE PROPERTY OF 2D-C/SIC COMPOSITES (MT) - LIN JiangRong; YANG ChengPeng; QI YunChao (Jixie qiangdu)
In order to characterize the Ⅰ-Ⅱ mixed-mode fracture performance of 2D-C/SiC composites, Arcan butterfly specimens with unilateral cracks were used, and the mode-Ⅰ and mode-Ⅱ fracture shape factors of the specimen were calibrated through finite element model. The Arcan disc device was used to carry out mode-Ⅰ, mode-Ⅱ and Ⅰ-Ⅱ mixed-mode fracture tests upon 2D-C/SiC butterfly specimens, and the macroscopic and microscopic fracture modes and strength properties of the specimens under different loading paths were investigated. The results show that the fracture toughness of mode-II of 2D-C/SiC material is higher than that of mode-I. With increasing of the loading angle, the influence of shear stress on the crack propagation path increases, and meanwhile the fracture resistance of the specimens presents a tendency to increase. The applicability of several fracture criteria is demonstrated, and an Ⅰ-Ⅱ mixed-mode fracture criterion for 2D-C/SiC composites is suggested.